Flexible manufacturing network creation. An alternative strategy to combat increased competition in the Single Market? - van ALFEN, J. R. (European Spatial Research and Policy, 1997)
In the recent years there has been (a) an increase in competition due to the creation of the Single Market, (b) a need for components instead of single sub-assemblies and (c) a dramatic economic success in the Third ltaly. All three events have made the creation of flexible manufacturing networks an interesting altemative to improve competitiveness among small- and medium-sized companies in areas where such networks do not exist yet. This article looks at what is already known about the creation of flexible manufacturing networks. Besides some common aspects, like determinants, life-cycles, support organisations and network brokers, it gives a description of three empirical models. These are the industrial districts or Third Italy model, the Danish model and the Appalachian Center for Economic Networks model. Their functioning and pros and cons are explained to help areas willing to run a network creation scheme.